The timechart of biblical history. - Atrium (Chippenham : Third Milenium Press, 2002)
Old testament - Genesis - Mozes - Exodus - A land of milk and honey - The kingdom of Saul, David, Solomon, Judah and Israel - The jewish captivities Ancient Jerusalem - The New Testament world - The ten commandments - The Lord's prayer